ผลของกรรมวิธีทางความร้อนต่อโครงสร้างจุลภาคและสมบัติทางกลของเหล็กกล้าไร้สนิม 25Cr-35Ni ภายหลังจากการใช้งานที่อุณหภูมิสูงภายใต้บรรยากาศคาร์บูไรซิ่ง - กรรณิการ์ เหมทัศน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This present research work studies and investigates the effect of carburization and effect of reheat treatment conditions of 25Cr- 35Ni or HP alloy after long-term service under high temperature carburization atmosphere on microstructures and hardness and tensile strength in order to prolong life time for further service. The as-received cast HP alloy microstructure consisted of carbide network and films in very high amount, resulted in higher hardness but lower tensile strength and elongation. The as-received alloy specimens were reheat treated for solutioning treatment at temperatures of 1,100, 1,150 and 1,200°C for 6 hours then each aged at temperatures of 800, 900 and 1,000°C for 24 hours. From the results, it showed that the amount of carbide phase vastly decreased after applying reheat treatment in all conditions. Furthermore, the tensile strength and elongation of all reheat treated specimens were increased comparing to the as-received one. The specimens which solutioning treated at 1200ºC had lowest amounts of carbide but highest tensile strength value when compare with the others.